Dissent among Muslims on Qunut, Maulud, and Nisfu Sya’ban: Study on Bid’ah Cinta Film - Indah Fadhilla; Siti Napsiyah; Balyan Rabaz (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2023)
Differences in opinion among Muslims, commonly known as ikhtilaf, are the theme raised by the film Bid’ah Cinta. Through the plot analysis proposed by Tzvetan Todorov, it can be seen that the conflict in the movie is in the middle plot two Muslim clerics’ different opinions about Qunut, Maulud Nabi, and Nisfu Sya’ban. At the beginning of the film plot, the life of the people is still balanced. However, the conflict occurs in the middle one of the plot. In the final plot, conditions return to balance. Each character has agreed to remain harmonious amidst these opinion differences. This study uses qualitative methods to investigate every scene in the film. These scenes show a picture of ikhtilaf and the community’s responses to these differences. This study aims to show that differences of opinion in Islam, as depicted in Bid’ah Cinta film, will raise social conflicts if they are not wisely solved. This film conveys that fellow Muslims must accept differences and maintain good faith to create harmonious relations in the community.